PENGARUH REKRUTMEN, KOMUNIKASI INTERPERSONAL, DAN KREATIVITAS TERHADAP KINERJA KARYAWAN PANAMA BALI STORE - Luh Kadek Budi Martini; A.A.I.Ngurah Dyah Prami; Ni Luh Gede Pratiwi Anjeni; Ni Komang Prasiani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
The main objective of this study was to analyze the effect of recruitment, interpersonal communication, and creativity on the performance of Panama Bali Store employees. This research is a descriptive study using a quantitative approach. The sample is determined by the census method of 40 respondents. data collected by interview technique, documentation, and questionnaires. Data were analyzed using a Likert scale and multiple linear regression. The results of the study found that recruitment had a positive and significant effect on employee performance, interpersonal communication had a positive and significant effect on employee performance, creativity had a positive and significant effect on employee performance on interpersonal communication and creativity had a positive and simultaneous effect on employee performance in Panama Bali Store. Recruitment research, interpersonal communication, and creativity are needed to create and improve better employee performance to support company performance.